Identification of a mimotope of a complex gp41 human immunodeficiency virus epitope related to a non-structural protein of Hepacivirus previously implicated in Kawasaki disease - Hakimuddin Sojar; Sarah Baron; Mark D. Hicar (Microbiology Spectrum)
ABSTRACT Current HIV vaccine strategies are hampered by difficulty with recapitulating heavily mutated broadly neutralizing antibodies. We have previously isolated a highly mutated antibody termed “group C 76-Q13-6F5” (6F5) that uses immunoglobulin heavy chain variable region (VH)1-02. 6F5 targets a conformational epitope on HIV gp41 and mediates Ab-dependent cell cytotoxicity (ADCC). Reverting the group C 76 antibodies’ variable chain to VH1-02 germline in antibody 76Canc showed retained ADCC activity. A vaccine targeting an epitope functionally recognized by germline antibodies offers a distinct advantage. Due to the 76Canc germline antibody ability to retain anti-HIV function, we sought to identify a protein target that could form the basis of a vaccine. 76Canc specifically recognized a number of acidic peptides on a microarray containing 29,127 linear peptides. Meme analysis identified a peptide sequence similar to a non-structural protein of Hepacivirus previously implicated in Kawasaki disease (KD). Binding was confirmed to significant peptides, including the Hepacivirus-related and KD-related peptide. On serum competition studies using samples from children with KD compared to controls, targeting of this epitope showed no specific correlation to the clinical syndrome of KD. Yeast-displayed human protein microarray autoantigen screening was also reassuring. This study identifies a peptide that can mimic the gp41 epitope targeted by 76C group antibodies (i.e., a mimotope). We show little risk of autoimmune targeting inclusive of inflammation similar to KD, implying non-specific humoral immunity targeting of similar peptides during KD. Development of an HIV vaccine based on such peptides should proceed, but with continued caution.IMPORTANCEThe development of protective HIV vaccines continues to remain a significant challenge. Many of the broadly neutralizing antibodies require a significant number of mutations, suggesting that traditional vaccines will not be able to recapitulate these types of responses. We have discovered an antibody that has Ab dependent cell cytotoxicity (ADCC) activity against HIV even when mutating the heavy chain of that antibody to germline. As a potential target for vaccines, this offers a distinct advantage: a few immunizations should directly stimulate B cells harboring those specific germline variable chains for expansion. This study sought to identify potential peptide targets that could be formulated into such a vaccine. We identified a peptide that both germline and mature antibodies can recognize. Initial autoantigen screens and consideration of inflammatory disorders suggest this identified antigen is a feasible approach to move forward into pre-clinical models.